SPECIAL PSYCHOLOGY AS A POST-CLASSICAL SCIENCE - Kobylchenko , Vadim Volodymyrovych; Omelchenko , Iryna Mykolayivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article reveals theoretical and methodological approaches to understanding special psychology as a post-nonclassical science.